Transfection Of Hepg2 Cells With Bacteriophages T7 And M13 Displaying Regions Of Hepatitis B Surface Antigen - Tang, Kie Hie (2008)

(untitled)
Hepatitis B is a major public health problem worldwide that may lead to chronic liver diseases, cirrhosis and hepatocellular carcinoma. It is caused by hepatitis B virus (HBV) which is responsible for 500,000 deaths annually. The preS domain of HBV particularly amino acids 21-47, is believed to be involved in the initial step of HBV infection through attachment to hepatocyte. In order to study virus-cell interactions, both T7 and M13 bacteriophages have been genetically modified to display regions of Hepatitis B surface antigens. In the present study, the recombinant T7 and M13 phages were used to transfect human hepatocarcinoma cell line HepG2. Interestingly, T7-PreS1/2 carrying the second half of preS1 (residues 60-108), but not T7-PreS1/1 which carried the first half of preS1 (residues 1-47), was demonstrated to be the most effective in transfecting HepG2 cells in a dose- and time-dependant manner. The DNA of phage could be recovered from cell lysate and confirmed by PCR whereas infectious form of internalized phage was measured by plaque forming assay. Under fluorescence microscope, internalized phage exhibited the appearance as fluorescent dots. On the other hand, M13-PreS carrying the preS region showed low efficiency of transfection, thus suggesting that the interaction is also dependant on the valency of targeting ligand. Surprisingly, unmodified phages (MOI ≈ 1.25 × 105) were also capable of transfecting HepG2 at low efficiency and were thought to be taken up by nonspecific uptake. Dynamic light scattering analysis has been carried out to determine the thermostability of recombinant phages. The display of HBV surface antigen did not affect the stability of phages since no significant differences in thermostability were observed between control and recombinant phages. The ability and stability of recombinant phages to transfect HepG2 cells demonstrate the potential of phage displayed system as gene therapy for liver cancer.